(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study examined the influence of job stress on burnout among academic staff of polytechnics in Southwest Nigeria. A descriptive survey research design was employed, utilizing a multi-stage sampling technique. The population comprised all academic staff of polytechnics in Southwest Nigeria, with a sample of 480 participants selected through multi-stage random sampling. Data were collected using the Job-Related Tension Index (JRTI), developed by Kahn, Wolfe, Quinn, Snock, and Rosenthal (1964), to assess job stress, and the Maslach Burnout Inventory (MBI), developed by Maslach and Jackson (1986), to measure burnout. The findings revealed a significant influence of job stress on burnout among the academic staff (t(478) = -5.26, p < .01), with a strong positive correlation between job stress and burnout (r = .72, p < .01). Additionally, no significant gender differences were observed in burnout levels (t(478) = -0.92, p > .05). The study contributes to the existing body of knowledge and offers recommendations to polytechnic management, regulatory bodies, and government on policies and strategies to mitigate burnout among academic staff.